Intumescent coating: Scientific evidence of effective halogen-free fireproofing coating - Siti Maznah, Kabeb; Azman, Hassan (Penerbit UMP, 2023)
Our journey in producing this book has been a long one before this textbook made its way to you. A truly committed team of authors, editors, graphic designers and publishing experts worked together to produce something that has never been done before. This book contains several chapters including the introduction of flame retardant, the classification of flame retardant materials with a brief discussion of halogencontaining flame retardant, nanofiller-containing flame retardant, and inorganic flame retardant. A discussion on the FR mechanism is also devoted to the readership. The comprehensive information about intumescent flame retardant coating and the synergistic effect of nanofillers on flame retardancy properties have been inclusively discussed in this book. The detailed description of the mechanism of intumescent flame retardant as well as its advantages and its disadvantages have been thoroughly deliberated. Emphasis is placed on the recent developments in the field of fire testing and analysis of the fire performance of steel elements protected with intumescent coatings. These are followed by the new study on flame retardancy and thermal stability of hybrid nanofiller's intumescent flame retardant coatings. The hybridisation of the inorganic fillers and their effect on the coating performance are also proven through scientific evidence. The targeted audiences are industrial and academic researchers, industrial chemists, and fire safety engineers from the same field of study. It would also be beneficial for professionals within the materials science and engineering fields